ANGIOGRAPHY: RADIATION-HYGIENIC CHARACTERISTICS OF THE STAFF WORKING CONDITIONS - V. I. Kuzin (Радиационная гигиена)
Summarized information of the literature about dozes radiation of staff while carrying out angiography researching. Technical and dosimetric characteristics of  angiograph apparatus are represented. Analyzed radiation dozes of staff while carrying out researching of the brain vessels and carotid zones, angiogcardiograhpy, hepatic abdomen, renal and pelvic zones. Make conclusion that main directions of minimizing of dozes are protection  working places, using individual thyroid shields and protective  glasses, limiting number of carrying out researches by increasing number angiograph groups, technical improving apparatus and etc.